Ford in Toulon / Toulon in Ford - Max Saunders (Babel: Littératures Plurielles, 2021)
When Ford and his companion of the 1920s, Stella Bowen, visited Toulon at the end of 1925, she said she 'fell in love with Toulon at first sight'. Ford too was enamoured, and found he wrote well there. He was to revisit the town several times over the next few years, eventually renting part of the Villa Paul, near the sea, with Janice Biala in 1931. It was to be their main base in France until late 1936, when due to the Depression they could no longer afford to keep it on. The essay explores Ford’s life in Toulon with Bowen and their daughter Julie, and then with Biala. It will consider what they said about the region. But the main part of it will be devoted to discussing how Toulon and its environs figure in Ford’s writing; and in particular his pair of novels The Rash Act (1933) and Henry for Hugh (1934), both set in Toulon with recognisable descriptions of its features and landmarks. The aim is to gauge the difference Toulon made to Ford’s last two decades; how it changed not only his view of France but of himself. A conclusion describes the quest to locate the Villa Paul.